European differences in characteristics, treatments and outcomes in patients with non-ST-elevation myocardial infarction – novel insights from four national real-world registries. (25th November 2020) - Edfors, R; Jernberg, T; Lewinter, C; Eha, J; Asser, P; Andreka, P; Janosi, A; Jortveit, J; Halvorsen, S
Abstract: Background: Large-scale collection of standardized variables in patients with myocardial infarction (MI) in national real-world registries are only available in a few European countries and there is lack of cross-country comparisons. Purpose: To compare demography, risk factors, hospital treatment and short- and long-term survival in patients hospitalized for non-ST elevation MI (NSTEMI) in four different European countries. Methods: NSTEMI patients hospitalized and enrolled in national MI registries; EMIR (Estonia), HUMIR (Hungary), NORMI (Norway (2013–2016)) and SWEDEHEART (Sweden) from 2014 to 2017 were included. Results: In total 119, 191 patients with NSTEMI were included. The mean age at admission ranged from 70 years (Hungary) to 75 years (Estonia). The proportion of women was 36% in Sweden and 44% in Estonia. In Norway 24% were smokers, as compared to 17% in Sweden. Patients in Hungary had a high rate of diabetes mellitus (37%) and antihypertensive treatment (84%) but a low rate of lipid lowering treatment (32%). The proportion of patients with prior MI ranged from 28% (Norway) to 37% (Sweden). The presence of previous peripheral artery disease ranged from 7% (Sweden) to 17% (Hungary). The absolute proportion of performed coronary angiographies (58% versus 75%) and percutaneous coronary interventions (38% versus 56%), differed most between Norway and Hungary. Dual antiplatelet therapy ranged from 60% (Estonia) to 81% (Hungary) and statins from 78% (Norway) to 89% (Hungary), at discharge. The crude mortality rates at 1 month and 1 year are listed in table 1. Conclusion: Cross-comparison of four national European MI registries provide new insights in differences in risk factors, treatment and outcomes. Possible reasons for the observed differences, include differences in the underlying expected mortality in the populations, inclusion-criteria and coverage of the registries and variable definitions, that need to be further explored. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Estonian Research Council